(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the need for swimming pool facilities and infrastructure to support effective and safe Physical Education (Penjas) learning at Makassar State School 3. The research method uses a quantitative descriptive approach with survey, observation, and interview techniques, involving 20 respondents consisting of Penjas teachers, education staff, and students. The results of the study indicate that the overall level of adequacy of swimming pool facilities and infrastructure only reached 44%, which indicates inadequate conditions. The physical condition of the swimming pool is in the moderate category with a percentage of 66%, but the water quality and circulation system are still below standard. The availability of swimming learning facilities such as float boards, kickboards, and lane ropes is considered low with an average of only 52%, while safety facilities are in the most critical condition with adequacy of 18%, including the lack of lifeguards, safety signs, and emergency SOPs. Non-technical supporting facilities such as changing rooms, rinse rooms, and toilets are also at a moderate level of adequacy, namely 42%. These findings indicate that school swimming pool facilities and infrastructure do not support safe, effective, and sustainable swimming instruction. Therefore, strategic planning is needed to improve infrastructure, equip learning aids, and enhance safety systems to ensure optimal quality of physical education instruction.